Effect of modified atmosphere packaging (MAP) and postharvest treatments on quality of litchi fruits during storage - Ha, Pham Thi Thu; Mien, Nguyen Thi; Hien, Duong Thu; Tung, Nguyen Thanh; Trang, Nguyen Thi; Huong, Nguyen Thu (Vietnam Journal of Science and Technology, 2017)
In this article, effect of modified atmosphere packaging (MAP) and different postharvest treatments on quality of litchi (Litchi chinensis Sonn.) fruit was investigated. Quality indexes of litchi during cold storage at 4 ± 1 oC were measured in terms of decay, total soluble solids, titratable acidity, color, anthocyanin content and incidence of microbiological infection. These indexes were determined at harvest and 7, 14, 21, 28 and 35 days after storage. The results suggested that after 35 days of storage, the pericarp browning and fruit quality deterioration can be improved compared to the control by dipping fruit is hot water at 47 oC in 7 min., followed by oxalic acid solution (pH = 3 in 6 min.) and finally packed in MAP bag (LDPE, thickness of 30 µm incorporated 3-5 % silica additive) and stored at 4 ± 10C and relative humidity of 90 %.